Assessment of Diabetes Mellitus Perception among Adult Residents in Akure South Local Government Area of Ondo State, South West Nigeria (American Journal of Physical Education and Health Science, 2023)
The study aims at assessing the level of diabetes mellitus perception among the adults residing in Akure South local government areas of Ondo state. The pooled diabetes mellitus prevalence in Nigeria, according to the united nations estimate of 2017 is 5.77% this implies that 11.2 million Nigerians,(1 out of 17) adults are living with diabetes and this portends a dangerous trends for the country’s health development as has constituted a socio-economic burden on the nation. A descriptive cross-sectional method was adopted for the investigation. The sample consists of 332 residents of the study population area. A multistage sampling technique was used for the study. Data were collected through self-administered structure questionnaire and descriptive statistics (frequency table, proportion, mean and percentages) were used for the analysis. Secondary information was sourced from government publications, hospital records, group discussions, Health journals ,and relevant internet materials. The study revealed that majority of the respondents had adequate knowledge about diabetes mellitus. The finding also concluded that despite the good perception about diabetes among the adult residents, the disease prevalence and presentation are still high. The study thereby recommended increased awareness, engagement in physical exercise, consumption of balanced diets and regular screening for diabetes as preventive measures to control and /or reduce the mortality among the adult residents in Akure South Local Government.